Group I carcinogen infection, Helicobacter pylori, as a predisposing factor for Malt Lymphoma (Research, Society and Development, 2022)
The bacterium Helicobacter pylori (H. pylori) has an excellent ability to adapt, survive and colonize within acidic environments such as the gastrointestinal mucosa, causing numerous complications such as peptide ulcers, cancers, gastritis, and lymphomas, such as MALT lymphoma, being a B-cell neoplasm, subtype of non-Hodgkin's lymphoma. The objective of this work is to investigate what relationships exist between H. pylori infection and the characteristics and aspects of the emergence of MALT lymphoma. This study was carried out through a bibliographic survey in the following databases: Virtual Health Library (BVS), Scientific Electronic Library Online (SciELO), Latin American and Caribbean Literature on Health Sciences (LILACS) at PubMed (National Library of Medicine), with the help of the Health Sciences Descriptors (DeCS): Helicobacter pylori, MALT lymphoma and gastric lymphoma, grouped with the Boolean operator “AND” and “OR”. The inclusion criteria were free articles, in Portuguese and English, with a time frame from 2011 to 2022. The exclusion criteria were studies that were outside the proposed topic, repeated, incomplete, simple abstracts or reviews. The collection resulted in 112 articles, 47 were duplicates and another 65 were excluded by the quick reading of the title and abstract, leaving 30 studies read in full and after analysis another 18 were eliminated, leaving 12 articles to compose this research. As a result, and conclusion of the research, it was identified that H. pylori causes chemical and cellular changes, mainly inflammatory, resulting in cell imbalance and aging, making it a predisposing factor for MALT lymphoma.